The effect of exercising at home on physical, health and psychological aspects, in time of Corona virus (Covid 19) pandemic. - Bensemicha , Laid (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The study aimed to identify the degree of the level of trends of the study sample towards the effect of home exercise on the aspects (physical, health, and psychological), and to highlight the positive role of home exercise in helping a person to adhere to home quarantine through practice and the extent of its reflection on the aspects (physical, health, psychological) The researcher used the descriptive approach in the analytical study, and the study community was represented in the members of the local community of citizens residing in the state of Algeria quarantined at homes, and the sample reached (725) people, and an electronic questionnaire form was used through social media, The study showed that the degree of the level of trends of the study sample towards the impact of home exercise on the aspects (physical, health, and psychological) was high, in addition to the presence of sports tools, and the use of social media to aid in physical, health, and psychological development.